2010
DOI: 10.1016/j.molimm.2009.09.037
|View full text |Cite
|
Sign up to set email alerts
|

The P2 receptor antagonist PPADS abrogates LPS-induced neutrophil migration in the murine air pouch via inhibition of MIP-2 and KC production

Abstract: In this work, we show that P2 nucleotide receptors control lipopolysaccharide (LPS)-induced neutrophil migration in the mouse air pouch model. Neutrophil infiltration in LPS-treated air pouches was reduced by the intravenous (iv) administration of the non-selective P2 receptor antagonist PPADS but not by suramin and RB-2. In addition, the iv administration of a P2 receptor ligand, UTP, enhanced LPS-induced neutrophil migration. In contrast, the iv injection of UDP had no effect on neutrophil migration. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…In agreement with the latter role for neutrophils, we found that inhibition of early neutrophil migration in vivo by the P2 receptor antagonist, pyridoxalphosphate-6-azophenyl-29,49-disulfonic acid, decreased the release of the chemokines MIP-2 and KC (whose roles in mice are similar to those of IL-8 in humans), which reduced the migration of new neutrophils at the site of inflammation (41). A significant body of evidence further confirms our current observation that NTPDase1 expressed in neutrophils might play an important role in shaping immune responses.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In agreement with the latter role for neutrophils, we found that inhibition of early neutrophil migration in vivo by the P2 receptor antagonist, pyridoxalphosphate-6-azophenyl-29,49-disulfonic acid, decreased the release of the chemokines MIP-2 and KC (whose roles in mice are similar to those of IL-8 in humans), which reduced the migration of new neutrophils at the site of inflammation (41). A significant body of evidence further confirms our current observation that NTPDase1 expressed in neutrophils might play an important role in shaping immune responses.…”
Section: Discussionsupporting
confidence: 79%
“…Using the LPStreated air pouch as a model of acute inflammation with a predominant role of neutrophils, we observed that NTPDase1-KO mice produced more MIP-2 and KC than WT. Neutrophils represent .90% of all cells accumulated in the air pouch 4 h after LPS injection, and they contribute to MIP-2 and KC production in the air pouch (41). Therefore, this increased production of MIP-2 and KC in NTPDase1-KO mice could be due to neutrophil accumulation, which is maximal in the air pouch at this time point.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both KC and MIP‐2 play an important role in neutrophil migration, and these chemokines are mainly produced by macrophages 24–29 . The increase in number of neutrophils and macrophages in the peritoneal cavity of ATP‐injected mice raises the question of whether macrophages are involved in neutrophil migration.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, CXC ligand (CXCL) 8/IL‐8 plays a major role in neutrophil migration 21–23 . In mice, CXCL1/keratinocyte‐derived chemokine (KC) and CXCL2/macrophage inflammatory protein‐2 (MIP‐2), both murine functional homologues of IL‐8, recruit neutrophils to sites of injury and infection 24–29 . Also, anti‐KC neutralizing monoclonal antibody (mAb) and/or anti‐MIP‐2 neutralizing mAb suppress neutrophil migration and inflammation when injected in vivo into murine models of inflammation 27,30,31 .…”
Section: Introductionmentioning
confidence: 99%